On the changing colour of food and drink - Spence, C (Elsevier, 2019)
There is something of a tension between consistency and natural variation as far as the visual appearance properties of food and drink are concerned. While the majority of natural products tend to change their appearance as they age/ripen, many processed foods, by contrast, are specifically designed, or formulated, so as to maintain a consistent (optimal) visual appearance during the lifetime (or shelf-life) of the product. That said, food and beverage companies sometimes do suddenly change the colour of their products (e.g., to address legislation around the use of artificial food colours, as a result of changing consumer preferences/interests, or else simply to capture the consumers' attention on the shelf). A number of modernist chefs, especially those fond of molecular gastronomy/cuisine, and mixologists, have also become increasingly interested in (changing) the colour of the foods and drinks that they serve (either to surprise or entertain their guests, or else to play to the Instagram crowd). Intriguingly, several new chemical/technical means of changing the appearance properties of food and drink in real-time have been developed recently, thus raising the question of how people will respond. The context in which the colour change occurs, and the cause to which it is attributed, may well both play a key role in determining consumer acceptance of such novel rapid transformation of the appearance of food and drink, especially given the a widespread aversion amongst consumers to those food colours that are (perceived to be) artificial.